The Influence of Company Size, Company Growth, Leverage, and Liquidity on The Acceptance of Going Concern Opinion on Companies Listed on The Indonesia Stock Exchange in 2019 - Agista Eka Budiarti; Ni Nyoman Alit Triani (Universitas Islam Lamongan, 2021)
Going concern is the business continuity of a company that in shortly does not intend to liquidate or stop its operations. The auditor issues a going concern opinion to ensure the continuity of a company's business. The aim of this research is to decide the effect of company size, company growth, leverage, and liquidity ongoing concern audit opinion acceptance. The sample of this research used 602 companies listed on the IDX in 2019. Quantitative methods with logistic regression techniques were used in this study. The results showed that the size of the company affected on going-concern audit opinion. Meanwhile, company growth, leverage, and liquidity do not affect going concern audit assumption.